What Influences Chinese Adolescents’ Choice Intention between Playing Online Games and Learning? Application of Theory of Planned Behavior with Subjective Norm Manipulated as Peer Support and Parental Monitoring - Wang, Jia; Liu, Ru-De; Ding, Yi; Liu, Ying; Xu, Le; Zhen, Rui (Frontiers in Psychology, 2017)
This study investigated how and why Chinese adolescents choose between playing online games and doing homework, using the model of the theory of planned behavior (TPB) in which the subjective norm was manipulated as two sub-elements (peer support & parental monitoring). A total of 530 students from an elementary school and a middle school in China were asked to complete the measures assessing two predictors of TPB: attitude and perceived behavioral control (PBC). Next, they completed a survey about their choice intention between playing an online game and doing homework in three different situations, wherein a conflict between playing online games and doing homework was introduced and subjective norm was manipulated as that peers supported and parents objected to playing online games, respectively. The results showed that adolescents’ attitude and PBC, as well as the perception of obtaining or not obtaining support from their peers and caregivers (manipulated subjective norm), significantly influenced their choice intention in online gaming situations. These findings contribute to the understanding of the factors affecting adolescents’ online gaming, which has been a concern of both guardians and educators. With regard to the theoretical implications, this study extended previous work by providing evidence that TPB can be applied to analyze choice intention. Moreover, this study illuminated the effects of the separating factors of subjective norm on choice intention between playing online games and studying.